2023
DOI: 10.1089/trgh.2021.0148
|View full text |Cite
|
Sign up to set email alerts
|

Affirming and Inclusive Care Training for Medical Students and Residents to Reduce Health Disparities Experienced by Sexual and Gender Minorities: A Systematic Review

Abstract: Purpose: Providing inclusive and comprehensive gender-affirming care is critical to reducing health disparities (gaps in care) experienced by sexual and gender minorities (SGM). Currently, little is known about how medical students and residents are being trained to address the health needs of SGM persons or of the most effective methods. Methods: We conducted a systematic review of the research literature from 2000 to 2020 on the effectiveness of teaching medical stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Out of 27,090 articles screened and subjected to various inclusion and exclusion criteria and full-text review, 36 articles had educational intervention components that focused on transgender, gender-diverse, and gender-nonconforming care and medical students and/or residents. 17 All of the studies were qualitative studies having quasi-experimental and preexperimental (theoretical) designs. The majority focused on medical student training, with few including residents.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 27,090 articles screened and subjected to various inclusion and exclusion criteria and full-text review, 36 articles had educational intervention components that focused on transgender, gender-diverse, and gender-nonconforming care and medical students and/or residents. 17 All of the studies were qualitative studies having quasi-experimental and preexperimental (theoretical) designs. The majority focused on medical student training, with few including residents.…”
Section: Resultsmentioning
confidence: 99%
“…The CoP conducted a systematic review of the literature on each research topic to identify how medical schools in United States have addressed the topics in their educational curriculum and to identify the effectiveness of educational programs in addressing the needs of LGBTQ patients, people experiencing homelessness, and migrant farm workers on a series of topics, including: medical student/physician implicit bias, 44 interpersonal violence, 45 adverse childhood experiences, 46 opioid use, 47 pre-exposure prophylaxis, 48 affirming and inclusive care. 30 As part of our systematic reviews, we conducted searches of online databases (eg, MEDLINE/ PubMed, PsycINFO, Web of Science, Scopus, Ingenta, Science Direct, and Google Scholar) for original articles published in English and collected various study characteristics, including sample, study design, program format, program target, and pertinent outcomes. Effectiveness of interventions included those that increased knowledge about the health care needs of each of the 3 vulnerable populations, promoted positive attitudes toward them, increased comfort in working with them, and/or resulted in behavioral change.…”
Section: Practicementioning
confidence: 99%
“…29 Recent technological innovations in the communications sector have created new opportunities for online collaboration that allow individuals to meet in a virtual setting, eliminating geographical barriers (time zones notwithstanding) and transforming the traditional CoP into a virtual CoP (VCoP). Recent results of our own comprehensive review of literature of the successes of VCoP, 30 and a web-based survey of health care providers, 2 found satisfaction with the quality of shared knowledge, operations, and service provided by VCoP.…”
mentioning
confidence: 98%
“…Assessing medical students in clinical skills related to LGBTQ+ health—and not only on knowledge or self-reported competence—could better prepare students to address the persistent disparities in health and medical care that affect LGBTQ+ patients 13 . A recent review of 36 medical education interventions related to LGBTQ+ health found that only six included any assessment of skills, and typically only through self-report 14 . This gap in assessment can be filled by objective structured clinical examinations (OSCEs), which offer an opportunity to conduct performance-based evaluation of medical student competency in caring for LGBTQ+ patients, starting during the preclinical years 15 .…”
mentioning
confidence: 99%
“…13 A recent review of 36 medical education interventions related to LGBTQ+ health found that only six included any assessment of skills, and typically only through self-report. 14 This gap in assessment can be filled by objective structured clinical examinations (OSCEs), which offer an opportunity to conduct performance-based evaluation of medical student competency in caring for LGBTQ+ patients, starting during the preclinical years. 15 OSCEs also can provide structured exposure to LGBTQ+ health issues in clinical settings, especially when schools are limited in ensuring students' structured, planned clinical exposure to patients who identify as LGBTQ+.…”
mentioning
confidence: 99%